Fabrication of Polyaniline/TiO2 Nanocomposite Ammonia Vapor Sensor - S.G. Pawar; S.L. Patil; M.A. Chougule; P.R. Godse; D.K. Bandgar; V.B. Patil (Журнал нано- та електронної фізики)
Polyaniline/Titanium dioxide (PANi/TiO2) nanocomposite was fabricated from PANi, prepared by oxidative chemical polymerization and TiO2, synthesized by sol gel method. The PANi/TiO2 thin film sensors were prepared by spin coating technique. PANi/TiO2 nanocomposites were characterized by XRD and SEM. The cross sensitivity of thin film sensor indicate that the sensor exhibit selectivity to ammonia (NH3). The gas sensing measurements were carried out for different concentrations of NH3. The gas sensing study revealed that the response value increases with increasing concentration of NH3. Moreover, as concentration of NH3 increases, the response time decreases while recovery time increases, which can be attributed to the varying adsorption and desorption rates of an ambient gas with increasing concentration.